2010
DOI: 10.1007/s00223-010-9415-7
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Cortical Bone Microstructure in a Rat Model of Hypoxia-Induced Growth Retardation

Abstract: Little is known about hypoxia-induced modification of the canal network in the cortical bone despite its involvement in intracortical vascularity and bone blood supply. In this study, we examined the effect of chronic hypoxia on the canal network in postnatal bone. Tibiae were harvested from 4- and 8-week-old rats (hyp-4 and -8, n = 8 each), whose growth was retarded owing to postnatal exposure to hypoxia (12-14% O₂), and from 3- and 4-week-old normoxic rats (cnt-4 and -5, n = 8 each), which were similar in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Particularly, Schneider et al (46) found a significant difference between the anterior and posterior regions, citing a fourfold decrease in the canal volume density and a fivefold decrease in the canal number density in the posterior region compared with the anterior region. An analogous site dependency was found by Matsumoto et al (31) in rat tibiae harvested from 3-and 4-wk-old rats. Using monochromatic synchrotron radiation CT (SRCT), Matsumoto and colleagues found the posterior region of the tibia to be less porous than the anterior region.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Particularly, Schneider et al (46) found a significant difference between the anterior and posterior regions, citing a fourfold decrease in the canal volume density and a fivefold decrease in the canal number density in the posterior region compared with the anterior region. An analogous site dependency was found by Matsumoto et al (31) in rat tibiae harvested from 3-and 4-wk-old rats. Using monochromatic synchrotron radiation CT (SRCT), Matsumoto and colleagues found the posterior region of the tibia to be less porous than the anterior region.…”
Section: Discussionsupporting
confidence: 82%
“…Schneider et al (46) also observed a site dependence of mean canal orientation within mouse femora, although those findings found the anterior and medial regions to contain canals with a greater mean orientation. These differences in the spatial orientation of canals may be due to possible differences in a nonuniform load distribution in the tibia (31,49) in these two species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high detection sensitivity and quantitative performance of this type of imaging have been reported in angiography and lung imaging using iodine and xenon, respectively, as contrast agents. 28,29 Here, we focused on the zirconium dioxide k-edge that is close to the energy suitable for mCT imaging of rodent cortical bone 22,30 and developed ZrCA for sSRCT, which provides several advantages in bone microvascular imaging.…”
Section: Discussionmentioning
confidence: 99%
“…For rat tibial bone imaging at SPring-8, the 20-keV X-ray yielded good contrast with a high signal-to-noise ratio, allowing quantitative evaluation of its cortical microstructure and mineralization. 22,30 The zirconium dioxide k-edge (18 keV) is not far from 20 keV, and the light brilliance is as extremely high at 18 keV as at 20 keV in SPring-8 (http://www.spring8.or.jp/en/about_us/ whats_sr/sp8_features/). Thus, the X-ray energy close to 18 keV is ideal for not only separately imaging of vascular and bone microstructures of small or rodent bone specimen but also assessment of its mineral density, which shows regionto-region and time-to-time variations during bone repair.…”
Section: Discussionmentioning
confidence: 99%